Impact of Synthesis Method and Metal Salt Precursors on the CO2 Adsorption Performance of Layered Double Hydroxides Derived Mixed Metal Oxides - Cheah, Li Anne; Manohara, G. V.; Maroto-Valer, M. Mercedes; Garcia, Susana (Frontiers in Energy Research, 2022)
Since the 1990s, Mg-Al layered double hydroxide- (LDH-) based mixed metal oxides (MMOs) have emerged as promising CO2 capture sorbents. Despite the numerous attempts to improve these materials, the impact of the synthesis method and employed metal salt precursors on the properties of LDHs and MMOs remains unknown. In order to address this gap, the present study investigated how two common synthesis methods (i.e., co-precipitation and urea hydrolysis) and two different salt precursors (i.e., metal chlorides and metal nitrates) affected the physical properties of LDHs and CO2 capture performance of derived MMOs at intermediate temperature (200°C). The true chemical composition of the LDH phase was confirmed by the lattice parameter “a”, which reveals the Mg/Al ratios at the octahedral layers. The impact of synthesis methods and metal salt precursors was evaluated in terms of synthesis efficiency metrics (e.g., synthesis yield, purity, and percentage of unreacted reactants), and their relationship was studied with the CO2 adsorption behavior of MMOs in different aspects (e.g., adsorption capacities, kinetics, and cyclic stability). Pure MgO was used as a reference to assess the cyclic stability of MMOs sorbents. It was found that the LDHs synthesized by the co-precipitation method are superior in terms of high synthesis yields (∼100%), good LDH purity, high adsorption capacities, and kinetics. In contrast, the LDHs synthesized with the urea hydrolysis method are better in terms of cyclic stability but tend to have low synthesis yields (54%–81%) and LDH purity (containing many amorphous impurities of Al-based hydroxides).